Newborn with Hereditary Sensory and Autonomic Neuropathy Type- IV: A Case Report - Paul, Nibedita (Bangladesh Journal of Child Health, 2022)
Hereditary sensory and autonomic neuropathy type IV (HSAN-IV) is a very rare autosomal recessive disorder characterized by anhidrosis, recurrent fever, insensitivity to pain and temperature, hypotonia, and developmental delay. The most frequent complications of this disease are self-mutilation, febrile seizure, stroke, corneal scarring, multiple fractures, burn, osteomyelitis and joint deformities. There is no definitive treatment for this condition. Early diagnosis can reduce disease complications and number of cases. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 111-115